2022
DOI: 10.1111/vox.13361
|View full text |Cite
|
Sign up to set email alerts
|

International Society of Blood Transfusion Working Party on Red Cell Immunogenetics and Blood Group Terminology Report of Basel and three virtual business meetings: Update on blood group systems

Abstract: Background and Objectives Under the ISBT, the Working Party (WP) for Red Cell Immunogenetics and Blood Group Terminology is charged with ratifying blood group systems, antigens and alleles. This report presents the outcomes from four WP business meetings, one located in Basel in 2019 and three held as virtual meetings during the COVID‐19 pandemic in 2020 and 2021. Materials and Methods As in previous meetings, matters pertaining to blood group antigen nomenclature were discussed. New blood group systems and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…However, no relevant neutralizing activity in ABO has been found in another study [ 63 ], and the levels of SARS-CoV-2 neutralizing antibodies were also not significantly associated with the ABO Rh(D) group [ 50 ]. On the other hand, there are a total of 43 blood group systems with 345 distinct antigen specificities with variations in human populations [ 64 ] and only four basic ABO groups. It is suggested that the high simplification of the comparisons could result in residual confounding [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no relevant neutralizing activity in ABO has been found in another study [ 63 ], and the levels of SARS-CoV-2 neutralizing antibodies were also not significantly associated with the ABO Rh(D) group [ 50 ]. On the other hand, there are a total of 43 blood group systems with 345 distinct antigen specificities with variations in human populations [ 64 ] and only four basic ABO groups. It is suggested that the high simplification of the comparisons could result in residual confounding [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Support for this assumption comes from the fact that no blood group antigen has been discovered with prevalence >1% and <90% since 1989 for any of the blood group systems we studied. 7,[46][47][48][49] Out of 120 blood group antigens newly-discovered from 1990 to 2022 for any blood group system, 7,[46][47][48][49] only three have prevalence between 1% and 90% (KDAS, DACY, and YCAD of the Knops blood group system 49 ). The remaining 97.5% (117/120) are either high or low incidence antigens.…”
Section: Alphafold2-predicted Localization Of Kell Ser726pro and Bcam...mentioning
confidence: 99%
“…The Diego blood group system is comprised of 23 blood group antigens, three of which are high prevalence and 20 of which are low prevalence [ 1 ]. The Di a antigen was first identified in 1955, when the immune response to this antigen (in Mrs. Diego) was implicated in a fatal case of hemolytic disease of the fetus and newborn (HDFN) in Venezuela [ 2 ].…”
Section: Introductionmentioning
confidence: 99%